Asset Based Community Development Melalui Pendampingan Sertifikasi Halal Produk UMK Driyorejo Kabupaten Gresik - Kambali, Muhammad; Arif, Muhamad (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to increase the knowledge and capacity of Driyorejo MSE business actors in applying for self-declared halal certification as an effort to develop the competitiveness of business products. The method of implementing this service uses Asset-Based Community Development (ABCD) based assistance. The analytical instruments used are mapping, discovery, dream, define, design, and destiny. The results of this service show that (1) Business actors in Driyorejo District have a Business Identification Number (NIB) as the legality of licensing their business activities, (2) Business actors have halal certificates for food and beverage products that have been produced, and (3) Business actors are able to increase sales by increasing online marketing strategies by utilizing social media, such as TikTok, Instagram, and several other social media.